Figures and Jakarta's Image Deconstruction in Novel Jakarta Rock ‘n Roll by Sekar Ayu Asmara - Wanda Choirunisa; Fadlil Yani Ainusyamsi; Rohanda Rohanda (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
Superior views circulating in society can draw out small narratives, but in this novel, there are inferior views from many of society’s views. The purpose of this research is to find the binary opposition of figure and image of Jakarta in novel Jakarta Rock ‘n Roll by Sekar Ayu Asmara because many people still believe in the grand narrative. In fact, there are still many realities hidden behind the grand narrative. The researcher uses Derrida's deconstruction theory to find binary opposition in novels and uses the literature technique. In the stage of analysis, the researcher divides it into four stages, classification, reduction, analysis, and conclusions. The results of this study show deconstruction value contained in various characters from the public's view and image of Jakarta city which has the reverse side of many public views. This research contributes to seeing different views from common views in society that are universal. Universal values are reviewed through this research so that readers can see the inferior values of figures and image of Jakarta.